Surgery and Medical Treatment in Microprolactinoma: A Systematic Review and Meta-Analysis - Jianglong Lu; Lin Cai; Zerui Wu; Weiwei Lin; Jiadong Xu; Zhangzhang Zhu; Chengde Wang; Qun Li; Zhipeng Su (International Journal of Endocrinology)
Objective. Dopamine agonists (DAs) are recommended as the first-line treatment for prolactinomas; however, tumour recurrence after drug withdrawal remains a clinical problem. Recent studies have reported high remission rates via surgery in microprolactinomas. The aim of this systematic review and meta-analysis was to compare the clinical result of DA treatment with surgery as initial therapy in patients with treatment-naive microprolactinoma. Methods. A comprehensive literature search for studies and reports regarding microprolactinoma patients treated with DAs and/or surgery published between January 1970 and November 2020 was conducted using four electronic databases (PubMed, Embase, Google Scholar, and the Cochrane Library). Clinical treatment outcome was evaluated by the biochemical remission of serum prolactin level to normal after treatment. The I2 statistic was used to quantify heterogeneity. Pooled data were analysed according to a random effect model. Results. Eighteen studies with 661 patients were included for analysis. The DA treatment group achieved a higher remission rate at ≥12 months follow-up (96% vs. 86%; P=0.019). Surgery showed a higher remission rate than the DA treatment group after the treatment withdrawal (78% vs. 44%; P=0.003). Patients with preoperative prolactin level of ≤200 ng/mL had a higher remission rate than patients with preoperative prolactin level of >200 ng/mL (92% vs. 40%; P=0.029). Conclusion. Surgery showed a high remission rate in treatment-naive microprolactinoma patients after treatment withdrawal and may be an alternative first-line treatment strategy in addition to DAs, particularly in patients with a preoperative prolactin level of ≤200 ng/mL.